Case Report: Optical Coherence Tomography Usage for Treatment of the Chronically Lost Stent in the Left Main Coronary Artery - Krcmar, Tomislav; Grgic Romic, Ivana; Tomulic, Vjekoslav; Jakljevic, Tomislav; Bastiancic, Luka; Zeljkovic, Ivan (Frontiers in Cardiovascular Medicine, 2022)
Acute adverse outcomes of a stent loss during percutaneous coronary intervention (PCI) are well described, however, data on long-term consequences are scarce, especially with intravascular imaging. We report a case of a coronary stent loss in the left main and ostial left circumflex artery (LCx) bifurcation and its migration into the LCx ostium during PCI procedures. This rare complication, which was not immediately noticed, was verified and successfully resolved 5 months after using optical coherence tomography and right trans-radial access. Considering the infrequency of this complication, few cases have been reported, however, our case has several distinct specificities. We aim to encourage the crushing technique in cases of chronic stent loss when the retrieval is not an option and highlight the optical coherence tomography (OCT) value in imaging and evaluation of similar complex settings.